2007
DOI: 10.1002/ejoc.200601072
|View full text |Cite
|
Sign up to set email alerts
|

A New and Efficient Heterogeneous System for the Phthalimide N‐Oxyl (PINO) Radical Generation

Abstract: Sodium periodate/wet silica gel in the presence of dichloromethane is an efficient reagent at room temperature for the phthalimide N‐oxyl (PINO) radical generation from its precursor N‐hydroxyphthalimide (NHPI). PINO reactions with cycloalkenes occur exclusively by a “pure” radical mechanism, contrasting with PINO's behavior when it is generated using lead tetraacetate.(© Wiley‐VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2007)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…The safety problem becomes particularly serious for practical large‐scale production. Subsequently, organic oxidants including 2,2,6,6‐tetramethylpiperidin‐1‐oxyl and phthalimide‐ N ‐oxyl were reported for these reactions, but they are too expensive for industrial amplifications. Thus, many researchers have made continuing attempts to develop catalysts for achieving dehydrogenation without oxidants.…”
Section: Introductionmentioning
confidence: 99%
“…The safety problem becomes particularly serious for practical large‐scale production. Subsequently, organic oxidants including 2,2,6,6‐tetramethylpiperidin‐1‐oxyl and phthalimide‐ N ‐oxyl were reported for these reactions, but they are too expensive for industrial amplifications. Thus, many researchers have made continuing attempts to develop catalysts for achieving dehydrogenation without oxidants.…”
Section: Introductionmentioning
confidence: 99%
“…Later on, it was shown that cross-dehydrogenative coupling of NHPI with toluene proceeds in the presence of a variety of oxidants, (NH 4 ) 2 Ce(NO 3 ) 6 , PhI(OAc) 2 , KMnO 4 , Mn(OAc) 3 ·2H 2 O, Pb(OAc) 4 , or Co(OAc) 2 /O 2 to afford N -benzyloxyphthalimide in yields of 11–75% [ 255 ]. The oxidative coupling of NHPI with cyclohexene and cyclooctene using NaIO 4 in the CH 2 Cl 2 /H 2 O mixture in the presence of silica gel was documented [ 256 ]; the coupling products were only partially characterized (the NMR spectra of the crude compounds were reported). In another study, the oxidative coupling of NHPI with cyclic and acyclic alkenes was performed in the presence of (NH 4 ) 2 Ce(NO 3 ) 6 , Pb(OAc) 4 , or anthraquinone; in the case of metal-containing oxidizing agents, the radical reaction mechanism is suggested along with the competitive ionic mechanism; the reaction products and procedures for their synthesis were not completely characterized [ 257 ].…”
Section: Reviewmentioning
confidence: 99%
“…Also we have calculated dipole moments of compounds 1, 5a-e, 6 and 7 (Table 1) The results presented in Table 1 lead to the following observations: (i) the most negative net atomic charges on the hydroxyphthalimidic (NHPI) nitrogen atom are recorded for compounds with three nitro groups (5b), trifluoromethyl group (5c,d) or carboxyl groups (5e); (ii) the most net negative atomic charges on the NHPI oxygen atom are recorded for 2,4-dinitropyridine (6), picryl (5b) and NBD (7) derivatives; (iii) the most positive net atomic charge on the N-O-C carbon atom are recorded for the trifluoromethyl derivative (5c); and (iv) the highest dipole moment is recorded for NBD-derivative (7). No satisfactory correlation for experimental λ max (Table 1) vs. calculated λ max was obtained using dipole moments plus net atomic charges (Table 1), but Eq.…”
Section: Qspr Studiesmentioning
confidence: 99%
“…Recently, it has been used as a catalyst in oxidation processes, via the phthalimide N-oxyl radical [5] (known as PINO). The PINO radical can be obtained in several ways [5][6][7], and has an important role in the oxidation of a large variety of compounds, including aliphatic hydrocarbons [7,8], alkylbenzenes [9,10], alcohols and aliphatic amines [11,12], benzylamines [13], N-alkylamides [14], etc. O-Substituted hydroxylamines have found applications in medicinal chemistry, having antihistaminic and bactericidal properties, as well as being used as prophylactic chemicals in protecting animals against ionizing radiations [15,16].…”
Section: Introductionmentioning
confidence: 99%